Overview of adverse events notifications of compounded medicines in Brazil since VigiMed system implementation (Revista Contexto & Saúde, 2024)
Introduction. Unfavorable occurrences during drug treatment are considered adverse events, important causes of hospitalization, morbidity and mortality. Pharmacovigilance is responsible for monitoring these events, but there are few records of its application in compounding pharmacies. The aim of the study is to identify and quantify adverse events reports of compounded drugs received by the VigiMed system, from December 2018 to December 2022. Method: Retrospective, descriptive and quantitative study, carried out using VigiMed reports, extracted from the Brazilian Open Data Portal. The analysis of reports followed inclusion and exclusion criteria relevant to the topic. Results: Of the 67,109 reports received by VigiMed during the study period, 195 reports of suspected adverse events caused by compounded medication were identified, approximately 0.29% of the total. Heparin, silver nitrate and amiodarone were the active ingredients that showed the highest absolute frequencies in reports. Antidepressants, anxiolytics, anorectics and antiobesic, drugs subject to special sanitary control in Brazil, were also identified. The most frequent route of administration was injectable (94), followed by oral (50) and ophthalmic (25). Conclusions: The results obtained allow concluding the great diversity of active substances present in the reports, with the highest occurrence for compounded drugs indicated for injectable and oral use, therefore of systemic effect, which requires greater care in preparation and vigilance in use. It was found that, although the pharmacist is the main notifier of suspected adverse events to compounded drugs, the practice of pharmacovigilance in this context is little performed or still incipient in Brazil.
Keywords: Pharmacovigilance; Pharmaceutical compounding; Adverse events; VigiMed